LITERATUR RIVIEW: IMPLEMENTASI BRAIN BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA DITINJAU DARI TINGKAT PENDIDIKAN - Kama Rinduka, Hermien; Abdul Aziz; Eko Andy Purnomo (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
This study is useful for systematically reviewing the application of the Brain Based Learning model in mathematics learning at various levels of education. Guided by PRISMA and using Systematic Literature Review as the method in this study, 30 articles published in the period 2020–2025 were analyzed to identify the effectiveness of BBL on students' mathematical abilities. The results show that BBL has a consistent positive effect on improving creative, logical, critical, connective, reflective, and mathematical communication skills. At the elementary school level, concrete and enjoyable learning, such as BBL, which has been proven to be efficient, is needed to improve conceptual understanding and creativity. At the junior high school level, this model strengthens logical thinking and mathematical literacy skills with the support of digital media such as GeoGebra and Wordwall. Meanwhile, at the high school level, BBL contributes to improving reflective and critical thinking skills and mathematical representation. Overall, BBL is capable of creating active, meaningful, and student-centered mathematics learning and developing Higher Order Thinking Skills (HOTS), which are in line with the learning requirements of the 21st century.